2017
DOI: 10.1007/s11418-017-1146-x
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of Entada phaseoloides and Entada rheedei

Abstract: The aim of our study is to find functional compounds from natural resources. We focus on plants grown in tropical areas, especially Madagascar and Thailand, because they have unique flora and are expected to contain interesting compounds. We review the functional compounds of the seed kernels of Entada phaseoloides and E. rheedei and their biological activities such as anti-proliferation and melanogenesis inhibitory properties, etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In the previous reports, many active compounds have been isolated from E. phaseoloides seeds and stems such as quercetin, luteolin, apigenin, and kaempferol. 6 To propose the active compounds in AEP, its profile was analyzed by HPLC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous reports, many active compounds have been isolated from E. phaseoloides seeds and stems such as quercetin, luteolin, apigenin, and kaempferol. 6 To propose the active compounds in AEP, its profile was analyzed by HPLC.…”
Section: Resultsmentioning
confidence: 99%
“…The seeds of Entada species are utilized as a folk medicine to treat skin disease and as a soap in Indonesia, Thailand, and other tropical countries. 5,6 However, the biological activities of the leaves of E. phaseoloides are barely mentioned. To reduce intracellular ROS levels could be a good way to avoid UVB-induced human epidermal keratinocytes (HaCaT cells) apoptosis and skin damage.…”
Section: Introductionmentioning
confidence: 99%
“…Entadamide A showed potential anti melanin inhibition with activity similar to arbutin, a common cosmetic ingredient (Sugimoto et al 2018). Therefore, entadamide A could be responsible for inhibiting tyrosinase as a solute in the ethanol solvent.…”
Section: Anti-tyrosinase Activitymentioning
confidence: 99%
“…By altering TGF-signalling, lowering MMP-1 and MMP-2 expression, and reducing the synthesis of type I collagen in human dermal fibroblasts, EGCG inhibits TGF- receptors. These characteristics suggested that EGCG may have anti-scarring capabilities [ 100 ].…”
Section: Wound Healing Strategiesmentioning
confidence: 99%